2022
DOI: 10.3390/children9121817
|View full text |Cite
|
Sign up to set email alerts
|

A Pediatric Case of Inverted Meckel’s Diverticulum Presenting with Cyclic Vomiting-like Symptoms: A Case Report and Literature Review

Abstract: Asymptomatic Meckel’s diverticulum cases are not uncommon, leading to diagnostic difficulties in cases of atypical presentations with only gastrointestinal symptoms other than bloody stool. A nine-year-old boy diagnosed as having cyclic vomiting because of recurrent abdominal pain and vomiting for 6 months was referred to our institute and hospitalized due to worsening symptoms. After admission, abdominal ultrasonography showed the multiple concentric ring sign and a pseudokidney sign at the lower ileum, leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This may be associated with massive gastrointestinal bleeding ( 4 , 5 , 7 , 8 ) and diverticular inversion. Endo et al ( 17 ) found that radionuclide scanning imaging may not be effective in the diagnosis of MD with inversion, and the diagnostic rate of DBE for these cases was 100%. The nuclide is easily dispersed and difficult to concentrate in the case of massive hemorrhage of digestive tract.…”
Section: Discussionmentioning
confidence: 99%
“…This may be associated with massive gastrointestinal bleeding ( 4 , 5 , 7 , 8 ) and diverticular inversion. Endo et al ( 17 ) found that radionuclide scanning imaging may not be effective in the diagnosis of MD with inversion, and the diagnostic rate of DBE for these cases was 100%. The nuclide is easily dispersed and difficult to concentrate in the case of massive hemorrhage of digestive tract.…”
Section: Discussionmentioning
confidence: 99%
“…Another type of complication that can occur is inversion of the diverticulum, which may lead to intussusception. Yorishi et al performed a literature review on cases of inverted Meckel diverticulum and found 31 cases with intussusception out of 74 cases with inverted MD [15].…”
Section: Discussionmentioning
confidence: 99%